KONSEP DAN MODEL FITUR E-CRM PADA LAYANAN TIKET TRANSPORTASI ONLINE DI WILAYAH PURWOKERTO JAWA TENGAH - Irfan Santiko; Ade Irma Suryani (Jurnal Akrab Juara, 2019)
Internet network users are increasing and everyone has their own busy lives. This can happen to people who usually use transportation services to travel outside the city and the internet network can be used as a liaison between the transportation and also customers. To help customers make online bookings, both door-to-door and point-to-point transportation, choosing a schedule and destination location as needed, a study is carried out, which is making a ticket reservation feature for web-based transportation agents. E-Ticketing is one of the results of the development of Customer Relationship Management (CRM) features where digital areas in the business are the basis of service products. However, not all transportation service companies know the basis of CRM and how to implement the actual or minimum standards that can be applied in accordance with the business strategies used in customer service.